Measurement of the ratio of B+c branching fractions to J/psi pi+ and J/psi mu+nu mu final states - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The first measurement that relates semileptonic and hadronic decay rates of the B+c meson is performed using proton-proton collision data corresponding to 1.0 fb−1 of integrated luminosity collected with the LHCb detector. The measured value of the ratio of branching fractions, B(B+c→J/ψπ+)/B(B+c→J/ψμ+νμ)=0.0469±0.0028(stat)±0.0046(syst), is at the lower end of available theoretical predictions.
Im Titel ist "pi" als griechische Buchstaben dargestellt
Im Titel ist "mu" als griechische Buchstaben dargestellt
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel ist "nu" als griechischer Buchstabe dargestellt
Im Titel ist + hochgestellt